PAK MULTIKULTURAL DALAM BINGKAI ERA REVOLUSI INDUSTI 4.0 - Novistianus D. Salenussa; Beatrix J.M. Salenussa (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2019)
This writing aims to provide ideas for Christian Religion Education (PAK) in the frame of the industrial revolution 4.0 era to answer the multicultural context in Maluku. This writing uses qualitative description approach with an inductive and hermeneutic approach to analyze the data relating to the multicultural context of society in Maluku and the Role of Christian Religious Education to help people to openly accept plurality in the era of the industrial revolution 4.0 This illustrates that the role of religion can be used as a guide in an effort to create a meaningful, peaceful and dignified life. In line with that, education is used as an effort for human to be able to develop their potential through a learning process that is known and recognized by the community, to be creative in conveying learning which increasingly plays a central role in cyber technology in human life, so that in the continuation of Christian Religious Education can also be used as learning in an effort to increase spiritual potential, in order to form people who have faith, character, and noble according to the challenges of the growing eraKeyword: Christian Religion Education (PAK), Multicultural, Industrial Revolution 4.0